2022
DOI: 10.3389/fbioe.2022.1023231
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized multidimensional biomaterials for bone microenvironment engineering applications: Focus on osteoimmunomodulation

Abstract: As bone biology develops, it is gradually recognized that bone regeneration is a pathophysiological process that requires the simultaneous participation of multiple systems. With the introduction of osteoimmunology, the interplay between the immune system and the musculoskeletal diseases has been the conceptual framework for a thorough understanding of both systems and the advancement of osteoimmunomodulaty biomaterials. Various therapeutic strategies which include intervention of the surface characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…As a category of bone biomaterials with immunomodulatory properties, GO-based nanocomposites are of particular interest. Investigating their immunomodulatory mechanisms may provide clues for the development of bone biomaterials with similar properties [ 98 , 99 ]. Su et al confirmed that GO coatings could modulate macrophage polarization and cytokine secretion via Toll-like receptors.…”
Section: Potential Mechanisms and Related Signaling Pathways Of Graph...mentioning
confidence: 99%
“…As a category of bone biomaterials with immunomodulatory properties, GO-based nanocomposites are of particular interest. Investigating their immunomodulatory mechanisms may provide clues for the development of bone biomaterials with similar properties [ 98 , 99 ]. Su et al confirmed that GO coatings could modulate macrophage polarization and cytokine secretion via Toll-like receptors.…”
Section: Potential Mechanisms and Related Signaling Pathways Of Graph...mentioning
confidence: 99%
“…[ 4 ] However, most biomaterials produce a complex inflammatory response that is difficult to manipulate after implantation and may inhibit bone regeneration owing to the slow degradation of biomaterials, which may produce a persistent chronic inflammatory response. [ 16 ] Therefore, biomaterials that can adequately activate the early inflammatory response and promote the regression of subsequent inflammation are required to accelerate bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] However, most natural organic polymers, such as collagen, fibrin, gelatin, sodium alginate, cellulose, and hyaluronic acid, exhibit anti‐inflammatory properties. [ 16 ] Hydroxyapatite and calcium phosphate have been shown to have pro‐inflammatory properties, promoting the expression of pro‐inflammatory factors, such as IL‐1 and IL‐6, and also act as vaccine adjuvants to enhance the immune response. [ 17 ] However, their slow degradation rates may lead to chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%